A Clinical and Laboratory Approach to the Evaluation of Innate Immunity in Pediatric CVID Patients - Kutukculer, Necil; Azarsiz, Elif; Karaca, Neslihan Edeer; Ulusoy, Ezgi; Koturoglu, Guldane; Aksu, Guzide (Frontiers in Immunology, 2015)
Defective adaptive immune responses are well studied in common variable immune deficiency (CVID) patients; however more focus is needed on innate immune system defects to explain CVID’s clinical and laboratory heterogeneity. This is the first study comparing migratory function of granulocytes, oxidative burst activity of phagocytic cells, surface integrin expressions on neutrophils and lymphocytes, NK cell numbers and cytotoxic activity, NKT cells, lymphocyte subsets such as CD8+CD28+, CD4+CTLA-4+ cells in CVID patients (n:20) and healthy controls (n:26). The relationship between laboratory findings and some clinical was also investigated. CD3+CD8+ T cytotoxic cells were found to be elevated in CVID patients, but CD3+CD8+CD28+ or CD3+CD8+CD28- cells did not show any significant difference. CD4+CTLA-4+ cell percentages were significantly lower in CVID patients compared to healthy controls. Severe CVID patients had decreased percentages of NK cells with increased NK cell cytotoxicity suggesting possibly increased activation. Furthermore, CD3-CD16+CD56+CD28+ cells of CVID patients were elevated while percentage of CD28- NK cells was decreased. Neutrophil migration percentages were lower but and oxidative burst activity was not affected. CD11a expressions on these cells were depressed in contrast to increased expression of CD18. Innate immunity defects may affect the extent of recurrence and severity of infections in CVID. Our observations highlight some of these associations and indicate the need for further similar studies for improving better innate system evaluation batteries for these patients. Further phenotypic correlations of these analyses will help clinicians reach a more definitive target for the molecular genetic diagnostic of pediatric CVID patients.